The Doctor: A Novel Based on the Life of Dr. George Goodfellow - More, Clay (Thorndike, Maine : Center Point Large Print, 2021)
"In Tombstone, Arizona Territory, the town too tough to die, Dr. George Goodfellow is known as the Surgeon to the Gunfighters. Friends with the Earp brothers and Doc Holliday, his services as a doctor are needed in the aftermath of the Gunfight at the O.K. Corral, but Goodfellow is handy with a gun and his fists, too, and he needs those skills to survive when hes stalked by a crazed miner and has to untangle a deadly murder mystery! The West of the Big River series continues with The Doctor, an all-new, exciting novel based on actual historical characters and incidents by acclaimed Western author Clay More. One of the most stirring time periods in Old West history comes to vivid life in this tale of vengeance and heroism and a frontier sawbones dedicated to healing"--
Keywords: Goodfellow, George Emory, -- 1855-1910 -- Fiction; Surgeons -- Arizona; Fiction; Biographical fiction